A new cytochrome P450 from Drosophila melanogaster, CYP4G15, expressed in the nervous system. - Maibeche-Coisne, M.; Monti-Dedieu, L.; Aragon, S.; Dauphin-Villemant, C. (Biochemical and Biophysical Research Communications, 2000)
A novel cytochrome P450 was isolated from Drosophila melanogaster by PCR strategy with primers deduced from the crayfish Orconectes limosus CYP4C15 sequence, which is supposed to be involved in ecdysteroid biosynthesis. The full-length cDNA contains a 1980 bp open reading frame encoding a predicted protein of 574 amino acids and was designated CYP4G15. The corresponding gene is located at 10C1 on the X chromosome. The presence of a N-terminal segment mainly hydrophobic indicated that the corresponding enzyme is probably microsomal. In situ hybridization demonstrated predominant expression of CYP4G15 in the brain of third larval instar and Northern-blots showed no overexpression in insecticide resistant strain. This is the first indication of a specific P450 expressed in the central nervous system of Drosophila, and the putative function of the corresponding enzyme is discussed.